Matan Jurumiyah Is Not For The Novice Arabic Learners: A Critical Study Text - Alimin Alimin; Zainal Abidin; Muslihin Sultan; Muhaimin Muhaimin; Fahmi Gunawan (Arabic Education Program IAIN Pekalongan, 2021)
Albeit the studies on Matan Jurumiyah Book have been extensively conducted, few studies have been focusing on the critical content of Kitab Matan Jurumiyah. To fill the gap, this research aims to examine why Matan Jurumiyah Book is not applicable for novice Arabic learners. To collect the data, observation and in-depth interviews were conducted. The results of the study show that the material of the Matan Jurumiyah is not relevant to be used for the novice learners due to (1) the conciseness and condensation of the book contents, (2) the lackness of Arabic basic knowledge, (3) the raising of new problems for novice learners because of the number of syarah or explanation over the Book of Matan Jurumiyah. That empirical evidence was anchored to the internal and external factors. Internal factors are closely related to the dichotomy of syntax and morphology while external factors are related to the absence of consideration of the Indonesian context and are arranged in a deductive way. Therefore, this study recommends empirical, contextual, and policy implications for the readers.